Geographical Variation in the Use of Oral Anticoagulation and Clinical Outcomes among Patients with Atrial Fibrillation in Denmark, Sweden, and Finland - Frost, Lars; Halminen, Olli; Lehto, Mika; Airaksinen, K E. Juhani; Andersson, Tomas; Wändell, Per; Holzmann, Martin; Cordsen, Pia; Vinter, Nicklas; Johnsen, Søren Paaske (TH Open, 2023)
Background Geographical mapping of variations in the treatment and outcomes of a disease is a valuable tool for identifying inequity. We examined international and intranational variations in initiating oral anticoagulation (OAC) therapy and clinical outcomes among patients with atrial fibrillation (AF) in Nordic countries. We also tracked real-world trends in initiating OAC and the clinical outcomes.Methods We conducted a registry-based multinational cohort study of OAC-naive patients with an incident hospital diagnosis of AF in Denmark (N = 61,345), Sweden (N = 124,120), and Finland (N = 59,855) and a CHA2DS2-VASc score of ≥1 in men and ≥2 in women between 2012 and 2017. Initiation of OAC therapy was defined as dispensing at least one prescription between 90 days before and 90 days after the AF diagnosis. Clinical outcomes included ischemic stroke, intracerebral hemorrhage, intracranial bleeding, other major bleeding, and all-cause mortality.Results The proportion of patients initiating OAC therapy ranged from 67.7% (95% CI: 67.5–68.0) in Sweden to 69.6% (95% CI: 69.2–70.0) in Finland, with intranational variation. The 1-year risk of stroke varied from 1.9% (95% CI: 1.8–2.0) in Sweden and Finland to 2.3% (95% CI: 2.2–2.4) in Denmark, with intranational variation. The initiation of OAC therapy increased with a preference for direct oral anticoagulants over warfarin. The risk of ischemic stroke decreased with no increase in intracranial and intracerebral bleeding.Conclusion We documented inter- and intranational variation in initiating OAC therapy and clinical outcomes across Nordic countries. Adherence to structured care of patients with AF could reduce future variation.
Keywords: atrial fibrillation; anticoagulation; bleed; geographical variation; stroke